(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This study examined the technical and scale efficiencies of irrigated tomato under Kano river irrigation project (KRIP) phase I. Primary data were collected from 213 irrigated tomato farmers, using multi-stage sampling techniques in three local government areas covered by KRIP. Data collected was based on the 2014/2015 irrigation farming season using structured questionnaire and were analysed using two-stage Data Envelopment Analysis (DEA). The study established that given the current level of output, small scale farms can produce output using less inputs at 30% and 34% on average. However, 21% of the 152 small scale farms are fully efficient under the variable return to scale while only 17% farms are fully efficient under constant return to scale, indicating that many over 80% of the small scale farms did not operate at an efficient scale, hence adjusting the scale of operation could improve the efficiency. Also, majority (92%) of the medium scale farms category were found operating in the region of increasing returns or the sub-optimal region. This is closely followed by 76% of large scale farm category. This indicates that medium and large scale farms are operating scale inefficiency or below optimum production scale. To achieve the optimum production scale, these farms could do so by decreasing the costs. It was therefore recommended that since the farms were operating below optimum production scale or scale inefficient, farmer-education should be encouraged by extension agents through effective and efficient dissemination of information.